Perbandingan Minat Belajar Menggunakan Google Meet dan Zoom Meeting di Perguruan Tinggi Keagamaan Islam Negeri - Yayuk Sri Rahayu; Guntur Kusuma; Ali Ridho (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
The study aimed to compare learning interests during the Covid-19 pandemic using the Google Meet and Zoom Meeting platforms in the distance learning process for PTKIN Sharia Banking Study Program students in East Java. The population in this study were students of the PTKIN Sharia Banking Study Program in East Java. The sampling method used is purposive sampling. This type of research is quantitative with an event study approach. The results of the comparison of student interest explained that the facility factor, economic factor, and convenience factor significantly differed from student learning interest using the Google Meet and Zoom Meeting platforms for PTKIN Islamic Banking Study Program students in East Java. In addition, the results of a comparison of students' interest in the Google Meet and Zoom Meeting platforms of PTKIN Islamic Banking Study Program students in East Java showed that students' interest in using the Google Meet platform was higher than that of students using the Zoom Meeting platform. That is because Google Meet is easy to access; when experiencing signal interruption, users can rejoin immediately and have no time limit during the learning process because it does not require a premium account.